IMPORTANCE PERFORMANCE ANALYSIS (IPA) DIMENSI KUALITAS PELAYAN JASA RUMAH SAKIT SELASIH TERHADAP KEPUASAN PASIEN (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
This research is intended to measure hospitalized patients' satisfaction toward dimension of Selasih Hospital service quality. It covers realibility, reponsiveness, assurance, emphaty, and tangibility. The researcher used close questions in collecting the primary data. She collected the data by using non probability sampling through convenience sampling. There were 170 patients taken as samples, they were divided into three classes; I, II and III. The used method of analysis is; the importance performance analysis, it is acknowledged that laboratorium check-up, doctor visit, immediate treatment; accurate and immediate check-up result, ineffective sophisticated equipment are not satisfactory to the customers. To ease these problems, the hospital management is expected to enhance medical staff competence and knowledge. The doctors, nurses and staffs commitment should also be enhanced so that they will always serve the patients well without distiguishing their classes. At last but not least, this hospital is suggested to cooperate with other hospitals which have adequate equipments.